36 Variable diagnostic accuracy in reading ecgs in a nurse-led primary pci pathway. (5th October 2017) - Canning, A; Peace, A; McNeill, A; Aleong, G; Bond, R; Finlay, D
Abstract : Background: The Electrocardiogram (ECG) remains as the crucial tool to diagnose acute ST-elevation myocardial infarction (STEMI). Activation of the cardiac catheterization team to perform Primary Percutaneous Coronary Intervention (PPCI) largely depends on the interpretation of the ECG at the time of first medical contact with the patient. In Northern Ireland, if the referrer decides that the ECG shows a STEMI they would then transmit the ECG to a designated Coronary Care Nurse who then decides whether to activate the PPCI pathway or to transfer the patient to the nearest Emergency Department (ED). Objective: We sought to ascertain the impact, ECG based decisions have on the PPCI pathway and specifically on clinical outcomes. Methods: ECG and clinical data were retrospectively reviewed for consecutive patients referred to the PPCI pathway over an 8-month period as part of a continuous audit. Patients were either accepted or turned down for PPCI by the Nurse. All ECGs were retrospectively adjudicated upon with a final diagnosis made by a senior Coronary Care nurse and Interventional Cardiologist. ECG interpretation was evaluated in the referrer group, the ECG machine, and the nurse activator. Results: A total of 344 patients were referred to the PPCI pathway over the 8-month period. 114 (33%) were accepted for PPCI. All accepted patients met diagnostic ECG criteria with 97/114 (85%) having a final diagnosis of STEMI. 230 referrals (67%) were turned down for PPCI, predominantly on the basis of lack of diagnostic criteria. All turndowns were considered appropriate. Paramedics were the main referrers 205/344 (60%) with the remainder from ED. The ECG machine suggested an ischaemic diagnosis in 95/97 (Sensitivity=98%) of patients with STEMI and 103/198 (1-Specificity=52%, Specificity=48%) of the turndown cases (patients with a final diagnosis of ACS/angina were excluded from the turndown group when calculating machine specificity). Of those referred for PPCI, 66% of the ED referrals were turned down. Of those referred by Paramedics for PPCI 67% were turned down. The STEMI group were significantly younger that the turndown group (63 ± 12 vs. 68 ± 17, p<0.01) with higher mortality in the turndown group at 12 months (17.1% vs. 10.5%). No STEMIs were missed. Conclusions: ECG interpretation by referrers in this nurse-led primary PCI pathway is sub-optimal. The high rate of false positives in ECG machine diagnoses in the turndown group could be an influencing factor in the human-decision making. There is a need to find ways to improve ECG interpretation, particularly in a time critical PPCI pathway.